2022
DOI: 10.3389/fpubh.2022.1038409
|View full text |Cite
|
Sign up to set email alerts
|

The public and patient involvement imperative in Ireland: Building on policy drivers

Abstract: What can we learn from the history of Public and Patient Involvement (PPI) in healthcare and research across global jurisdictions? Depending on region and context, the terminology and heritage of involvement in research vary. In this paper, we draw on global traditions to explore dominant themes and key considerations and critiques pertaining to PPI in order to inform a PPI culture shift in Ireland. We then describe the heritage of PPI in Ireland and present the case for combining methodological imperatives wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…A lack of and consistency in reporting more generally is also warranted, underscored in this review by a clear lack of discussion pertaining to facilitators, benefits, barriers and ethical issues to be extracted from the captured literature. This is not a new issue, and a call for researchers to consider reporting in a consistent way was highlighted by Gilfoyle et al 5. Researchers should strongly consider utilising frameworks like the ‘Guidance for Reporting Involvement of Patients and the Public 2’ (GRIPP2),89 which would help address this gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A lack of and consistency in reporting more generally is also warranted, underscored in this review by a clear lack of discussion pertaining to facilitators, benefits, barriers and ethical issues to be extracted from the captured literature. This is not a new issue, and a call for researchers to consider reporting in a consistent way was highlighted by Gilfoyle et al 5. Researchers should strongly consider utilising frameworks like the ‘Guidance for Reporting Involvement of Patients and the Public 2’ (GRIPP2),89 which would help address this gap.…”
Section: Discussionmentioning
confidence: 99%
“…PPI is recognised as a moral, methodological and policy imperative, and has become mandated across many jurisdictions and funding bodies globally, driving a rich, diverse and international evidence base 1–4. Specifically, evidence shows that involving patients and the public throughout the research process (ie, from research conceptualisation to dissemination) improves the research process and outcomes, such as the relevancy, credibility and effectiveness of knowledge being produced 5–8. For example, a systematic review by Baldwin et al 7 evaluated the impact of involving older adults in health and social care research as coresearchers and found an array of benefits for the academic researchers (eg, new learning from coresearchers experiences and perspectives), older adult coresearchers (eg, gaining new knowledge and skills), as well as benefits for the research quality and impact (eg, richer data).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPI in Ireland has been a focal priority for funders and health researchers since 2014 28 . This priority sparked capacity‐building initiatives, including the launch of the PPI Ignite Award in 2017, where five universities across Ireland were funded as individual PPI Ignite Teams by the Irish Health Research Board (HRB) and Irish Research Council (IRC).…”
Section: Methodsmentioning
confidence: 99%
“…PPI in Ireland has been a focal priority for funders and health researchers since 2014. 28 This priority sparked capacity‐building initiatives, including the launch of the PPI Ignite Award in 2017, where five universities across Ireland were funded as individual PPI Ignite Teams by the Irish Health Research Board (HRB) and Irish Research Council (IRC). Expanding on this progress, HRB and IRC funded the national PPI Ignite Network (March 2021–2026), ‘aim[ing] to provide a shared voice for PPI across Ireland, aiming to change the research culture, and an important contributor to improving health outcomes for the public’.…”
Section: Methodsmentioning
confidence: 99%